2018
DOI: 10.3389/fendo.2018.00700
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Hypothyroidism in Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis

Abstract: Background: The association between subclinical hypothyroidism (SCH) and polycystic ovary syndrome (PCOS) has been reported in several studies, but it is not well-recognized. The aim of this study was to evaluate the prevalence of SCH in women with PCOS.Methods: An extensive literature search was conducted in PubMed, Embase, Web of Science, and Cochrane Library databases. All articles published before May 2018 was considered for eligibility. No language restrictions were implemented. The prevalence of SCH in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 47 publications
1
22
1
2
Order By: Relevance
“…A recent meta-analysis suggested that women with PCOS became more prone to SCH [36]. We did find that SCH worsens glucose metabolism and lipid metabolism in PCOS women.…”
Section: Discussioncontrasting
confidence: 47%
“…A recent meta-analysis suggested that women with PCOS became more prone to SCH [36]. We did find that SCH worsens glucose metabolism and lipid metabolism in PCOS women.…”
Section: Discussioncontrasting
confidence: 47%
“…AITD has been observed in 18%–40% of women with PCOS [ 64 ]. Incidence of SHypo, goiters, and thyroid autoimmunity is higher among females with PCOS, and they have higher anti-TPO levels, larger thyroid volumes, and more hypoechogenic thyroids than those without [ 63 , 65 , 66 ]. In euthyroid patients with PCOS, higher TSH is associated with increased prevalence of hyperandrogenic phenotype [ 67 ].…”
Section: Metabolic Dysfunctionsmentioning
confidence: 99%
“…In women with PCOS, compared with those without the condition, higher TSH levels, anti-thyroid antibody positivity rate, and prevalence of thyroid disorders, particularly HT, have been demonstrated in three independent meta-analyses conducted to date ( 9 , 229 , 230 ). Based on six studies, the combined OR of SCH risk for women with PCOS (compared with healthy women) was 2.87 (95% confidence interval (CI), 1.82–9.92; p < 10 -6 ), assuming a TSH cut-off level of > 2.5 mIU/L, and 3.59 (95% CI, 2.25–5.73; p < 10 -6 ) when limiting TSH to ≥ 4 mIU/L ( 229 ). Similarly, two meta-analyses indicated a significant association between PCOS and the presence of AITD: one included six studies (OR = 4.81; 95% CI, 2.88–8.04; p < 10 -5 ) ( 9 ) and the other included 13 studies (OR = 3.27; 95% CI, 2.32–4.63; p < 10 -4 ) ( 230 ).…”
Section: Joint Prevalence Of Polycystic Ovary Syndrome and Autoimmunementioning
confidence: 99%